2003
DOI: 10.1038/sj.ijo.0802396
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and health-related quality of life: a cross-sectional analysis of the US population

Abstract: OBJECTIVE: To examine the relationship between body mass index (BMI) and health-related quality-of-life (HRQL), in the presence of dietary controls and/or exercise in a national sample in the United States. METHODS: BMI and its association with HRQL domains (physical, mental and activity limitations) were examined using the Centers' for Disease Control and Prevention's 2000 Behavioral Risk Factor Surveillence System (BRFSS) data, after adjusting for various sociodemographic factors, self-reported health-status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
181
5
12

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(213 citation statements)
references
References 18 publications
15
181
5
12
Order By: Relevance
“…Increased adiposity has been associated with poorer measures of SWB, including physical and psychological well-being in the able-bodied population. 29 We observed that individuals with SCI who considered themselves to be overweight reported less satisfaction with life and greater depressive symptoms than individuals who did not consider themselves to be overweight. One plausible explanation for these findings is that individuals with SCI who reported being overweight may have encountered greater limitations in accomplishing activities of daily living or community integration, therefore, becoming less satisfied with their life and experiencing more feelings of depression.…”
Section: Discussionmentioning
confidence: 60%
“…Increased adiposity has been associated with poorer measures of SWB, including physical and psychological well-being in the able-bodied population. 29 We observed that individuals with SCI who considered themselves to be overweight reported less satisfaction with life and greater depressive symptoms than individuals who did not consider themselves to be overweight. One plausible explanation for these findings is that individuals with SCI who reported being overweight may have encountered greater limitations in accomplishing activities of daily living or community integration, therefore, becoming less satisfied with their life and experiencing more feelings of depression.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have suggested that obesity is associated with impaired mental HRQOL. [18][19][20][21][22] However, other studies do not support this association, 14,15,17,23,24 and a few have even reported better mental health among people with excess body weight. [25][26][27][28] The discordant results from these studies may be due in part to methodological limitations.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In other crosssectional analyses, physically active individuals reported fewer unhealthy days (physical or mental), 10-12 though this finding is not universal. 13 Cross-sectional research also suggests physical activity is associated with greater well-being, successful aging and improved global quality of life, 4, 14-16 though some studies have found no association. 17, 18 The equivocal results may be due to differences in research design and the small sample sizes employed in some studies.…”
Section: Introductionmentioning
confidence: 99%